Case Report: A Case of Acute Cellular Rejection Due to Atopic Dermatitis Exacerbation 3 Years After Heart Transplantation - Kakuda, Nobutaka; Amiya, Eisuke; Hatano, Masaru; Maki, Hisataka; Bujo, Chie; Tsuji, Masaki; Narita, Koichi; Fujita, Kanna; Ishida, Junichi; Ono, Minoru; Komuro, Issei (Frontiers in Immunology, 2021)
Background Little evidence has been presented about the association between previous atopic/allergic disease and graft rejection after solid organ transplantation. Thus, we present a case wherein acute cellular rejection (ACR) after heart transplantation (HTx) was noted along with exacerbation of atopic disease. Case summary A 32-year-old man was admitted at our hospital for regular monitoring of graft rejection. He had undergone heart transplant 3 years prior due to dilated cardiomyopathy. Echocardiogram revealed good biventricular function, and no abnormal findings were found in blood sampling tests. However, biopsy showed moderate ACR (Grade 2R(ISHLT 2004)/3A(ISHLT 1990)), which required twice-repeated steroid pulses with intensified immunosuppression. Meanwhile, his atopic dermatitis, which was diagnosed before having heart failure, was getting worse for the past 6 months. The exacerbation of atopic dermatitis was presumed to be related to the development of the intractable cellular rejection. Discussion This case suggested the association of atopic disease and graft rejection after HTx. We examined 76 patients from a cohort of previous studies who underwent HTx at our hospital, which suggested that patients with atopic/allergic disorders such as atopic dermatitis and asthma tended to have a significantly higher frequency of moderate rejection than non-allergic patients. (p = 0.012; Fisher's exact test). Our case also suggests that exacerbation of atopic dermatitis might cause graft rejection of the transplanted organ, so that it is important to carefully evaluate the risk of graft rejection if there is a previous history of atopic/allergic disease.